Sense of coherence and associated factors among university students in China: cross-sectional evidence - Janet Junqing Chu; Mobarak Hossain Khan; Heiko J. Jahn; Alexander Kraemer (BMC, 2016)
Abstract Background Sense of Coherence (SOC) is considered as a health-promoting resource; it is mainly developed before the age of 30. The multiple demands university students face, such as study-related stress and financial difficulty, could challenge their SOC development. This study aimed to: 1) investigate the association between SOC, socio-demographic and lifestyle-related characteristics; 2) assess the effect of perceived stress on SOC controlling for other variables among the Chinese university students. Analyses were done to derive a better view on possible strategies to strengthen students' SOC and with that to promote their health. Methods The data used were from a Chinese university student health survey (N = 1,853). Logistic regression analyses were used to explore the effects of varied socio-demographic, lifestyle-related variables on students' level of SOC, as well as the association between perceived stress and SOC controlling for other variables in the analysis. Results Both social support (OR = 2.56 [1.87-3.50]) and better performance compared with peers (OR = 1.64 [1.15-2.34]) were associated with a stronger SOC. Not feeling isolated at university (OR = 1.60 [1.04-2.47]) and satisfaction with the political situation (OR = 2.05 [1.57-2.67]) were also associated with a stronger SOC. This counts also for high health awareness (OR = 1.40 [1.05-1.87]) and nutrition importance (OR = 1.67 [1.04-2.69]). Perceived stress (OR = 0.81 [0.79-0.83]) was negatively associated with a strong SOC when controlling for socio-demographic and lifestyle-related variables. Conclusion We suggest integrating stress coping, emotion management training programmes as well as measures promoting social integration for students and teachers at campus, promoting healthy behaviours, and creating a supportive learning environment as strategies for enhancing the SOC level of university students in China.